Analysis of the quality of service of the tourist sector in frontier city - Ruiz Andrade, José Gabriel; Martínez Moreno, Omaira Cecilia; Verján Quiñones, Ricardo (Corporación Universitaria Americana, 2023)
This article has focused on measuring the quality of service and customer satisfaction of the hotel sector in the border city of Tijuana, located in the northwestern part of Mexico. For data collection, a survey consisting of multiple-choice questions was applied to a guest sample that was calculated using a deliberate probabilistic sampling that determined the amount to be polled. It was defined as the profile of the respondent, guests who will be checking out (check out) within the hotel facilities. The results reflect the need to implement strategies that contribute to elevating the quality of service that guests receive from the hotels subject to analysis.